Teaching strategies of fashion design tutors and its sustainability in Malaysia HLIs - Shazrim Shah, Raja Iskandar; Shaari, Nazlina (Universiti Putra Malaysia Press, 2020)
As well as developing student design and soft skills, design tutors need to ensure that students comply with professional practice standards. Using proper teaching strategy models, students need to be taught both the technical know-how to succeed in the industry and the soft skills to assist them in being responsible members of the community. Even though the design teaching strategies in Malaysian higher learning institutions (HLIs) are generally planned by the tutors, there has been little research on fashion design tutor teaching strategy awareness. Therefore, for this reason and because there have been concerns raised that HLIs tutors in Malaysia are inexperienced and have little industrial practice, which could significantly affect the learning and the sustainability of fashion design programs in Malaysia, this paper conducted a small descriptive survey based study on design teaching strategy awareness to gather primary information on teaching strategy differences in 38 tutors teaching on fashion design courses in Malaysian HLIs. It was found that a conceptual teaching strategy model framework for design-based tutors was needed to provide guidance on the development of fashion design teaching strategies, and that future research was needed on the most appropriate fashion design education strategies for a sustainable future.